Essential Oils: Extraction, Bioactivities, and Their Uses for Food Preservation - Tongnuanchan, Phakawat; Benjakul, Soottawat (Journal of food science, 2014)
Essential oils are concentrated liquids of complex mixtures of volatile compounds and can be extracted from several plant organs. Essential oils are a good source of several bioactive compounds, which possess antioxidative and antimicrobial properties. In addition, some essential oils have been used as medicine. Furthermore, the uses of essential oils have received increasing attention as the natural additives for the shelf‐life extension of food products, due to the risk in using synthetic preservatives. Essential oils can be incorporated into packaging, in which they can provide multifunctions termed “active or smart packaging.” Those essential oils are able to modify the matrix of packaging materials, thereby rendering the improved properties. This review covers up‐to‐date literatures on essential oils including sources, chemical composition, extraction methods, bioactivities, and their applications, particularly with the emphasis on preservation and the shelf‐life extension of food products.